A non‐parametric model of residual brand equity in hierarchical branding structures with application to US beer data. (7th February 2013) - Voleti, Sudhir; Ghosh, Pulak
Summary Product offerings in many grocery product categories in supermarkets display varied branding structures built around a discernible branding hierarchy typically comprising brands, subbrands and stock keeping units. Firms often want to know what contribution each layer in the brand hierarchy brings to overall product value, and precisely how much of this contribution comes from unique branding associations (we term this value contribution the 'residual equity' of that branding layer). We make the economic argument that, in mature product categories, profit maximizing firms would retain the upper levels of the branding structure only if they were value enhancing. Using only aggregate sales and product data, we develop a semiparametric Bayesian method for a market response model to estimate jointly the residual equity of each layer in the branding structure while accommodating certain a priori restrictions on the equity values. Our proposed model is simple yet flexible and avoids common drawbacks in extant approaches. We implement our model on AC Nielsen beer category data from US supermarkets. We find that residual equity exists, is sizable in magnitude and sales impact, is heterogeneous in occurrence across the branding structure, yields realistic brand valuations and bears managerially relevant insights and implications.